2011
DOI: 10.1007/s00464-011-1612-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of resource utilization and outcomes in laparoscopic Roux-en-Y gastric bypass: a multicenter analysis of 14,251 patients

Abstract: Age, sex, race, obesity, and some medical comorbidities affect outcomes and increase resource utilization. Optimization of modifiable factors and careful patient selection are needed to facilitate further improvement in outcomes and resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The mean operating time to perform laparoscopic RYGB in our series was similar to that previously reported in the literature [13, 19, 20, 22, 23]; however, considerable variability exists between studies [18, 24, 25]. Furthermore, a number of studies have suggested that a learning curve exists and influences operating times [13, 25, 26].…”
Section: Discussionsupporting
confidence: 84%
“…The mean operating time to perform laparoscopic RYGB in our series was similar to that previously reported in the literature [13, 19, 20, 22, 23]; however, considerable variability exists between studies [18, 24, 25]. Furthermore, a number of studies have suggested that a learning curve exists and influences operating times [13, 25, 26].…”
Section: Discussionsupporting
confidence: 84%
“…Meier-Kriesche et al analyzed the database of over 50,000 renal transplant recipients (1988e1997) from the United States Renal Data System (USRDS) and showed that the relative risk ratio for graft loss was 1.4 times higher in patients with a BMI >36 kg/m 2 , [77]. Preoperative dependence on dialysis has been shown to be one of the strongest predictors of postoperative complications after bariatric surgery [80]. Due to this most transplant centers have set body mass index limits over which patients are not considered eligible for transplant (35 kg/m 2 ).…”
Section: Role Of Bariatric Surgery In Transplant Candidatesmentioning
confidence: 99%
“…The growing experience with LRYGB has been accompanied by improved outcomes for patients as more cases are treated with this method. However, relevant to this discussion, preoperative dialysis dependence was found to be the biggest risk factor associated with postoperative complications (odds ratio [OR], 8.5; 95% confidence interval [CI], 2.3–32.3) (97). Analysis of complications from National Surgical Quality Improvement Program (NSQIP) revealed that 4 of 12 (33%) patients on dialysis had complications; half of the complications required a return to the operating room within 30 days.…”
Section: Treatment Of Obesity In Esrdmentioning
confidence: 99%
“…Analysis of complications from National Surgical Quality Improvement Program (NSQIP) revealed that 4 of 12 (33%) patients on dialysis had complications; half of the complications required a return to the operating room within 30 days. The reasons for renal comorbidities that affect outcomes are unclear, and further studies are needed to confirm these findings (97).…”
Section: Treatment Of Obesity In Esrdmentioning
confidence: 99%